2017
DOI: 10.1038/nmat4868
|View full text |Cite
|
Sign up to set email alerts
|

Antifogging abilities of model nanotextures

Abstract: Nanometre-scale features with special shapes impart a broad spectrum of unique properties to the surface of insects. These properties are essential for the animal's survival, and include the low light reflectance of moth eyes, the oil repellency of springtail carapaces and the ultra-adhesive nature of palmtree bugs. Antireflective mosquito eyes and cicada wings are also known to exhibit some antifogging and self-cleaning properties. In all cases, the combination of small feature size and optimal shape provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
292
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(297 citation statements)
references
References 34 publications
4
292
1
Order By: Relevance
“…In sharp contrast to lotus-like micro-and nanostructures, closely packed nanocones with smaller tip sizes and interspaces can prevent moisture penetration while minimizing solid-liquid interface adhesion, which is the key to generating the desired CMDSP function. [51] It should be noted that the self-jumping phenomenon of condensate microdrops is not unique in nature. For example, Buller's droplet effect is essentially a typical CMDSP effect that is exploited by basidiomycete fungi to actively eject their spores into the air.…”
Section: Biological Prototypes Of Cmdsp Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In sharp contrast to lotus-like micro-and nanostructures, closely packed nanocones with smaller tip sizes and interspaces can prevent moisture penetration while minimizing solid-liquid interface adhesion, which is the key to generating the desired CMDSP function. [51] It should be noted that the self-jumping phenomenon of condensate microdrops is not unique in nature. For example, Buller's droplet effect is essentially a typical CMDSP effect that is exploited by basidiomycete fungi to actively eject their spores into the air.…”
Section: Biological Prototypes Of Cmdsp Surfacesmentioning
confidence: 99%
“…[66][67][68][69] Second, their tip size should be as small as possible to minimize the interface adhesion. [31,50,51,[66][67][68][69] Third, the building blocks must have a certain height or depth to avoid the collapse of the suspended water bridges. [68] Following these design principles and inspired by nature, our group proposed and demonstrated that efficient self-propelling of small-scale condensed microdrops can be [5] Copyright 2007, Wiley-VCH.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
“…[19] Recently, Quéré and co-workers compared the water condensation behaviors of nanopillars (Sample A) and nanocones (Sample C) (Figure 3a 4 ) and demonstrated that the conical shape of a nanostructure is crucial for further enhancing its antifogging ability. [20] The conical geometry provides a Laplace expulsion out of the texture, prevents the formation of durable wet patches, maintains the liquid in a full Cassie state, even for isolated microdrops (Figure 3a 5 ). As shown in Figure 3a 6 , the antifogging behavior of nanocones markedly differs from that of nanopillars under realistic dew formation conditions, and nanocones exhibit great antifogging properties.…”
Section: Water Strider Leg: Self-removal Of Condensed Dropletsmentioning
confidence: 99%
“…[12] a 3 ) Droplets moved from the bottom to the top of the hairs. a 4 ) SEM images of the pillar textures in sample A and the cone textures in sample C. [20] a 5 ) Sketch showing the effect of the cone geometry: the droplets beneath a large drop can be reabsorbed. In addition, small droplets condensing in cones can reconfigure at the top of the cone.…”
Section: Shorebird Beak: Directional Liquid Transportmentioning
confidence: 99%
See 1 more Smart Citation